The Coextensive Circumstance- Parachordoma - Anubha, Bajaj (Journal of Clinical and Diagnostic Pathology, 2020)
Parachordoma is an extremely exceptional, peripherally situated soft tissue neoplasm arising at non axial locations. Also designated as soft tissue “myoepithelioma” or “mixed tumour”, the tumefaction histologically simulates a chordoma of axial skeleton and was referred to as “central chordoma” emerging within non- axial sites. Nevertheless, a distinctive immune profile categorises the lesion as a unique entity.
Keywords: Circumstance- Parachordoma